Effects of curcumin on haematological values, immunity, antioxidant status and resistance of rainbow trout (Oncorhynchus mykiss) against Aeromonas salmonicida subsp. achromogenes - Yonar, M. Enis; Yonar, Serpil Mise; Ispir, Unal; Ural, Mevlut Sener (Academic Press Ltd- Elsevier Science Ltd, 2019)
The present study was conducted to evaluate the effects of various levels of dietary curcumin on growth performance, haematological values, immunity and protection against Aeromonas salmonicida subsp. achromogenes infection in rainbow trout, Oncorhynchus mykiss. Fish were fed with diets containing different levels of curcumin; 0% (C), %1 (E1), %2 (E2) and %4 (E3), as treatment groups. After 8 weeks of feeding, the growth performance [weight gain (WG), specific growth rate (SGR) and feed conversion ratio (FCR)], haematological values [the red blood cell (RBC) count, haemoglobin (Hb) concentration, haematocrit (Ht) level and erythrocyte indices: mean corpuscular volume (MCV), mean corpuscular haemoglobin (MCH) and mean corpuscular haemoglobin concentration (MCHC)1, various immune parameters [white blood cell (WBC) count, oxidative radical production (nitroblue tetrazolium (NBT) assay), phagocytic activity (PA) and phagocytic index (PI), total protein (TP) and immunoglobulin M (IgM) levels, serum bactericidal (BA), lysozyme (LYZ) and myeloperoxidase (MPO) activities] and antioxidant capacity [tissue malondialdehyde (MDA) levels and superoxide dismutase (SOD), catalase (CAT) and glutathione peroxidase (GSH-Px) activities] were analysed. In addition, fish were challenged by Aeromonas salmonicida subsp. achromogenes and survival rate was recorded for 14 days. The results indicated that the growth performance was significantly influenced by the dietary curcumin levels, the maximal WG and SGR occurred at fish fed the diet containing 2% curcumin. Fish fed the diet containing curcumin had lower FCR than those fed the control diet. The RBC count, Hb concentration, and Ht level increased in the groups fed with curcumin when compared with the control group. However, there were no significant differences in the MCV, MCH and MCHC values among experimental groups. All the chosen immune parameters were enhanced in the groups fed diets containing curcumin. Also, the relative percentage survivals were higher in the groups fed with curcumin, especially in the E2 group, compared to the control. The dietary curcumin stimulated the SOD, CAT and GSH-Px activities in liver, head kidney and spleen as compared to the control group; however, a reverse trend was observed in the MDA levels of tissues. The highest values for haematological, immunological (except TP level of E3 group) and antioxidant parameters were found in the E2 group. These results collectively suggest that curcumin can be used in aquaculture to improve the growth, haematological values, immune responses, antioxidant capacity and disease resistance of rainbow trout, O. mykiss.
Keywords: Aeromonas salmonicida; Curcumin; Fish; Growth; Haematology; Immunity